2016
DOI: 10.1155/2016/1748065
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 Prevents Endothelial Dysfunction, Insulin Resistance, and Hepatic Lipid Accumulation inApoe−/−Mice Fed with High-Fat Diet

Abstract: Backgrounds. VitB6 deficiency has been associated with a number of adverse health effects. However, the effects of VitB6 in metabolic syndrome are poorly understood. Methods. VitB6 (50 mg/kg/day) was given to Apoe −/− mice with hkdigh-fat diet (HFD) for 8 weeks. Endothelial dysfunction, insulin resistance, and hepatic lipid contents were determined. Results. VitB6 administration remarkably increased acetylcholine-induced endothelium-dependent relaxation and decreased random blood glucose level in Apoe −/− mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 31 publications
5
50
1
2
Order By: Relevance
“…Traditionally, VitB6 may treat depression, stroke, anaemia, nausea during pregnancy, clogged arteries, eye diseases, diabetes and inflammation associated with rheumatoid arthritis . Recently, we have identified that VitB6 improves insulin resistance in Apoe −/− mice fed with high‐fat diet and prevents isocarbophos‐induced vascular dementia in rats . Here, we further demonstrated that VitB6 suppresses pulmonary inflammation by inhibiting macrophage activation, as reduced productions of TNF‐α and IL‐1β in vivo, consistent with other reports in patients with rheumatoid arthritis .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Traditionally, VitB6 may treat depression, stroke, anaemia, nausea during pregnancy, clogged arteries, eye diseases, diabetes and inflammation associated with rheumatoid arthritis . Recently, we have identified that VitB6 improves insulin resistance in Apoe −/− mice fed with high‐fat diet and prevents isocarbophos‐induced vascular dementia in rats . Here, we further demonstrated that VitB6 suppresses pulmonary inflammation by inhibiting macrophage activation, as reduced productions of TNF‐α and IL‐1β in vivo, consistent with other reports in patients with rheumatoid arthritis .…”
Section: Discussionsupporting
confidence: 89%
“…Traditionally, VitB6 may treat depression, stroke, anaemia, nausea during pregnancy, clogged arteries, eye diseases, diabetes and inflammation associated with rheumatoid arthritis. [28][29][30][31] Recently, we have identified that VitB6 improves insulin resistance in Apoe −/− mice fed with high-fat diet 32 and prevents isocarbophos-induced vascular dementia in rats. 33 Here, we further demonstrated that Mechanistically, we uncovered that the AMPK-DOK3 pathway contributes to the anti-inflammatory effects of VitB6 by inhibiting macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo or ex vivo organ chamber study was performed as we described previously3233. Rats were sacrificed under anesthesia by intravenous injection with pentobarbital sodium (30 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been suggested that vitamin B6 can affect insulin resistance by regulating adipogenesis-associated genes [87]. However, it has also been proposed that reduced levels of vitamin B6 may induce insulin resistance by increasing homocysteine levels in consequence of the disrupted activity of cystathionine-β-synthase (CBS) and cystathionine-γ-lyase (CGL), enzymes requiring vitamin B6 as coenzyme [88].…”
Section: Physical Exercise and Changes In Gut Microbiota In Obese Indmentioning
confidence: 99%